The Influence of Chronic Pain and Cognitive Function on Spatial-Numerical Processing - Spindler, Melanie; Koch, Katharina; Borisov, Elena; Özyurt, Jale; Sörös, Peter; Thiel, Christiane; Bantel, Carsten (Frontiers in Behavioral Neuroscience, 2018)
Chronic pain is linked to changes in cognitive function. However, little is known about its influence on number sense, despite the fact that intact numerical-spatial processing is a prerequisite for valid scale-based pain assessments. This study aimed to elucidate whether number sense is changed in chronic pain (CP), to determine if changes have an impact on pain assessments using pain rating scales and what patient factors might contribute. N=42 chronic pain patients and n=42 matched controls were analyzed (age range: 33-68 years). Numerical-spatial abilities were investigated by using number line tasks, where participants either estimated the position of a given number (position marking) or the value of a predefined mark (number naming). Pain intensity was assessed using numerical rating (NRS), verbal rating (VRS) and visual analogue scales (VAS). Additional measures included attention and working memory, verbal intelligence, medication and depression. Results revealed that in number naming, patients deviated more from expected responses than controls, and that VAS scores were significantly higher than both NRS and VRS and correlated with deviations in position making. Changes in number naming were predicted by pain intensity, sex and IQ but not by attention, memory or opioid medication. This article presents new insight on which cognitive mechanisms are influenced by chronic pain with the focus on numerical spatial abilities. It could therefore provide useful knowledge in developing new pain assessment tools specifically for patients suffering from chronic pain.